Strengthening Political Education for First-Time Voters Ahead of the 2024 Kudus Regional Election Through Entertainment Stages at IAIN Kudus - Alfiyan Yuliyanto; M. Nur Rofiq Addiansyah (Universitas Muhammadiyah Ponorogo, 2026)
Regional head elections or Pilkada are electoral processes at the local level organized by the KPU in the region with the principles of direct, general, free, secret, honest, and fair elections. One of the central roles performed by the KPU is conducting political education. This is also what the KPU of Kudus Regency has done. One of the target points in the KPU's socialization program is first-time voters. First-time voters in the Kudus Pilkada are a central focus due to their fantastic number, according to the KPU Kudus's voter list totaling 145,140 first-time voters. This research aims to examine the steps taken by the KPU of Kudus Regency to increase voter participation. This research aims to understand the steps taken by the KPU (General Elections Commission) of Kudus Regency in increasing voter participation. The research method we used is descriptive qualitative research and data collection through observation and in-depth interviews. The findings include the role of the KPU of Kudus Regency in enhancing the political participation of first-time voters through several means, including 'KPU Kudus Goes To Campus'. Conclusion: The role performed by the KPU of Kudus Regency in increasing political participation among first-time voters is already optimal, although the delivery of material is less comprehensive. Meanwhile, the factors influencing the increase in voter participation are political party factors, political socialization with volunteers, and political awareness factors.